2017
DOI: 10.1111/1467-9566.12605
|View full text |Cite
|
Sign up to set email alerts
|

The role of alcohol in identity construction among LGBT people: a qualitative study

Abstract: Research suggests that alcohol use and misuse are higher among lesbian, gay and bisexual than heterosexual populations, yet the social context of drinking in sexual minority communities has rarely been examined. To explore lesbian, gay, bisexual and transgender (LGBT) people's relationship with alcohol, we conducted seven focus groups (N = 33) with pre-existing groups of friends and work colleagues (18 to 52 years) in Scotland, UK. We identified and analysed patterns in our data using thematic analysis. Respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 50 publications
(66 reference statements)
1
35
0
Order By: Relevance
“…Ally and Eve identified as bisexual, and it may be that they experienced particular forms of imagined or real pressure to 'fit in' when engaging in the explicitly heteronormative context of a 'girls' night out' in mainstream bars and clubs (particularly as it might be normalised or even expected that lesbian or bisexual women would drink beer on the gay scene (see Emslie et al 2017)). In contrast, participants such as Nicole, Megan and Joannawho most enthusiastically talked about drinking 'girly' drinks and enjoying the way these drinks look and tasteall identified as heterosexual.…”
Section: Eve 24mentioning
confidence: 99%
“…Ally and Eve identified as bisexual, and it may be that they experienced particular forms of imagined or real pressure to 'fit in' when engaging in the explicitly heteronormative context of a 'girls' night out' in mainstream bars and clubs (particularly as it might be normalised or even expected that lesbian or bisexual women would drink beer on the gay scene (see Emslie et al 2017)). In contrast, participants such as Nicole, Megan and Joannawho most enthusiastically talked about drinking 'girly' drinks and enjoying the way these drinks look and tasteall identified as heterosexual.…”
Section: Eve 24mentioning
confidence: 99%
“…However, these individualistic discourses tend to “minimize the role of social structural limitations … in the formation of identities and life paths” ( Dobson, 2012 ), p371 As Dobson (2012) argues, navigating the contradictory discourses of postfeminist femininity is likely to be particularly difficult for young women from lower socio-economic groups, and the risks of failure are also likely to be greater. Our previous work with other authors has focused on the intersections between gender and sexuality ( Emslie, Lennox, Ireland, 2017 ), gender and age ( Emslie, Hunt, & Lyons, 2013 ; Emslie et al, 2015 ; Lyons, Emslie, & Hunt, 2014 ; Lyons, McCreanor et al, 2014 ; Lyons & Willott, 2008 ; Willott & Lyons, 2012 ), and gender and ethnicity ( Goodwin, Griffin, Lyons, McCreanor, & Moewaka Barnes, 2016 ) in relation to identity and drinking practices. This paper explores how gender and social class intersect and are embedded in identity and drinking practices.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that interventions to reduce drinking must acknowledge the social contexts in which alcohol is used ( Emslie, Lennox, & Ireland, 2017 ; Vagenas et al, 2017 ). Similarly, social support plays an integral role in health-related behaviors with profound social contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, social support plays an integral role in health-related behaviors with profound social contexts. Given that bars and clubs provide important public refuge for LGBTQ communities ( Emslie et al, 2017 ), a non-abstinence approach would allow individuals to continue to access a social resource embedded in LGBTQ culture. However, emerging evidence linking LGBTQ bars to increased rates of AUD and other substance use disorders among MSM indicates a potential need for interventions to address drinking norms in the community ( Cochran, Grella, & Mays, 2012 ; Stall et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%